Lead’s effects on oxygen consumption and ammonia excretion in the pink shrimp (Farfantepeneaus paulensis) in relation to salinity - Assami Doi, Sonia; Lisboa Collaço, Fátima; Ricardo Sturaro, Luiz Gustavo; Barbieri, Edison (O Mundo da Saúde, 2012)
The objective of this study was to provide information on the toxicity of lead to the pink shrimp (Farfantepeneaus paulensis) based on oxygen consumption and the excretion of ammonia at different salinity levels. Organisms were collected and analyzed in the Cananeia region, São Paulo, Brazil. The study of lead toxicity is very relevant for the history of the region, due to the high economic value of shrimps and the estimated future environmental impacts. 45 organisms were collected and acclimated with constant aeration. Five replicates were used for routine measurement of metabolism in salinities 10, 20 and 30 and temperature of 27 °C. Four different lead concentrations were tested: 0.04, 0.4, 0.08 and 2.12 mg/L, beyond control. Respirometers chambers were used for 60 minutes. Dissolved oxygen was determined by the method of Winkler and ammonia based on phenol spectrophotometric method. The average oxygen consumption and ammonia excretion were evaluated using analysis of variance (p <0.05). Results showed a predominant decrease in rates of ammonia excretion and oxygen consumption. This fact allows us to infer that there was a shift in the metabolic pattern of the organisms as regards detoxification and stabilization of metabolic patterns. Analysis of variance showed that oxygen consumption and ammonia excretion average lead concentrations of 0.8 and 2.12 mg/L were significantly different as compared to controls.